IMPLEMENTASI KEBIJAKAN PENERTIBAN PEMASANGAN REKLAME DI KOTA KALIANDA: (Studi Pada Satuan Polisi Pamong Praja Kabupaten Lampung Selatan) - Dirgantara, Sony; Pramazuly, Ayu Nadia; Mosshananza, Hinfa (Jurnal Progress Administrasi Publik, 2023)
The research aims to describe how the Implementation of the Regulation Policy for Billboard Installation in Kalianda City carried out by the South Lampung Regency Civil Service Police Unit as a Regional Enforcer in accordance with Regulation Number 16 of 2016. The background of this research is because there are still billboards installed not in accordance with applicable regulations, namely South Lampung Regent Regulation Number 20 of 2011 concerning Procedures for Granting Billboard Permits in South Lampung Regency. The Civil Service Police Unit is part of the members in implementing the regulation of billboard installation in Kalianda City.  This research method is carried out using qualitative methods. The indicators of this study use the theory of George C. Edward, namely 1) Communication, 2) Resources, 3) Disposition and 4) Bureaucratic Structure. The result of this study is that the implementation of billboard regulation in Kalinda City has gone quite well, but there are still inhibiting factors, namely 1) internal factors, still lack of facilities in implementation, 2) external factors, derived from human resources and part of the responsibility of the company.   Keywords : Implementation; Policy; Billboard.